The incubation of Tinfoil barb (Barbonymus schwanenfeldii) eggs using funnel system at different temperatures - Siska Mellisa; Rizki Danang Ramadhan; Iwan Hasri; Nurfadillah Nurfadillah (Depik, 2022)
Tinfoil barb (Barbonymus schwanenfeldii) is freshwater fish found in Borneo, Java, and Sumatera including in Aceh Province waters. It is known as a native species in Indonesia, locally known as Tengadak or Lampan and this species is popular for consumption due to its taste.  Tinfoil barb is targeted species of inland water for fisheries production. In recent years, the fish population has declined because of overexploitation and habitat degradation. Therefore, this study aimed to analyze the effects of temperature on Tinfoil barb (B. schwanenfeldii) eggs incubation using a funnel system. It was conducted at Balai Benih Ikan (BBI) Lukup Badak, Central Aceh Regency. The Completely Randomized Design was used as a statistical analysis method with four treatments and three replications at 22±1 oC, 25±1 oC, 28±1 oC, and 31±1 oC. Hatching was carried out using a funnel system with 100 grain/liter of eggs density for incubation. The parameters measured were hatching time and rate, egg yolk absorption time, the survival rate of the embryo, larvae abnormality, and water quality. The ANOVA test results showed that temperature significantly affected hatching time and rate, egg yolk absorption time, and larvae abnormality (P0.05). In contrast, the effect was insignificant on the survival rate of an embryo, with P0.05. It is concluded that the optimum temperatures for Tinfoil barb eggs incubation were about 25±1 oC–31±1 oC. A funnel system was more effective for incubation than the conventional system.Keywords:Tinfoil barbFishIncubationTemperatureFunnel System